First‐line therapy with dacomitinib, an orally available pan‐HER tyrosine kinase inhibitor, for locally advanced or metastatic penile squamous cell carcinoma: results of an open‐label, single‐arm, single‐centre, phase 2 study. (4th October 2017) - Necchi, Andrea; Lo Vullo, Salvatore; Perrone, Federica; Raggi, Daniele; Giannatempo, Patrizia; Calareso, Giuseppina; Nicolai, Nicola; Piva, Luigi; Biasoni, Davide; Catanzaro, Mario; Torelli, Tullio; Stagni, Silvia; et al.
Abstract : Objective: To harness the frontline therapy in advanced penile squamous cell carcinoma (PSCC), for which chemotherapy exerts moderate activity but poor efficacy. Dacomitinib is an irreversible, pan‐epidermal growth factor receptor (HER) inhibitor. Patients and Methods: In a phase 2 study (NCT01728233), patients received dacomitinib 45 mg/day, orally, continuously. Inclusion criteria were SCC histology, clinical stage N2–3 or M1 (Tumour‐Node‐Metastasis classification system 2009), and no prior chemotherapy administration. The primary endpoint was the objective response rate (ORR, according to the Response Evaluation Criteria in Solid Tumors, version 1.1). Stopping rules based on the Bayesian posterior probability (PP) to demonstrate that the ORR exceeded 20% were set. Results: From June 2013 to October 2016, 28 patients were treated. Eight (28.6%) had visceral metastases, 14 (50%) had pelvic and 17 (60.7%) clinically involved bilateral lymph nodes. One complete and eight partial responses were obtained (ORR 32.1%, 80% credibility interval 21.0–43.0%). The median (interquartile range [IQR]) follow‐up duration was 19.8 (6.3–25.7) months; 12‐month progression‐free survival was 26.2% (95% confidence interval [CI] 13.2–51.9); 12‐month overall survival (OS) was 54.9% (95% CI 36.4–82.8). The median (IQR) OS of locally advanced patients was 20 (11.1–not reached) months. The Bayesian PP of exceeding the 20% ORR target was 92.3%. Grade 3 adverse events (skin rash) were seen in three patients (10.7%). Tissue samples from 25 patients were analysed. Only two patients had high‐risk human papillomavirus‐positive tumours. Epidermal growth factor receptor (EGFR) amplification was found in four patients (equally responders and non‐responders) and it was confirmed in all post‐dacomitinib samples. Telomerase reverse transcriptase (TERT) mutations were found in responders only (60%), and phosphatidylinositol 3‐kinase/mammalian target of rapamycin (PI3K/mTOR) pathway gene mutations were found in 42.9% of responders vs 8.3% of non‐responders. Conclusion: Dacomitinib was active and well tolerated in patients with advanced PSCC and may represent an option when combined chemotherapy cannot be administered. Mutations in downstream effectors of EGFR signalling in relation to dacomitinib activity deserve further studies.